2020
DOI: 10.1111/anae.15201
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from intensive care in patients with COVID‐19: a systematic review and meta‐analysis of observational studies

Abstract: Summary The emergence of coronavirus disease 2019 (COVID‐19) has led to high demand for intensive care services worldwide. However, the mortality of patients admitted to the intensive care unit (ICU) with COVID‐19 is unclear. Here, we perform a systematic review and meta‐analysis, in line with PRISMA guidelines, to assess the reported ICU mortality for patients with confirmed COVID‐19. We searched MEDLINE, EMBASE, PubMed and Cochrane databases up to 31 May 2020 for studies reporting ICU mortality for adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
373
7
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(422 citation statements)
references
References 33 publications
34
373
7
8
Order By: Relevance
“…Taken together, our results are consistent with the recent nding by Armstrong et alof improved COVID-19 ICU outcome over time, which was attributed to increased ICU experience, and evolving admission criteria, treatments, and demographics [40]. We additionally hypothesize that aimprovements in reported mortalities over time and regions may arise as healthcare systems become less overwhelmed, and as more recent studies account for more complete patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Taken together, our results are consistent with the recent nding by Armstrong et alof improved COVID-19 ICU outcome over time, which was attributed to increased ICU experience, and evolving admission criteria, treatments, and demographics [40]. We additionally hypothesize that aimprovements in reported mortalities over time and regions may arise as healthcare systems become less overwhelmed, and as more recent studies account for more complete patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Our pooled ICU best case mortality rate of 28.3% (95% CI 0.27 to 0.32) amongst COVID-19 patients is lower than earlier reports from Wuhan's 78% [20] and Seattle's 85% [8], but in line with the more recent report of 31% from Atlanta [10], as well as 25.7% and 41.6% reported in reviews by Quah et al [39] and Armstrong et al [40] respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Reports from hospitals caring for patients during the initial outbreak in China indicated that at least 80% of patients with COVID-19 requiring mechanical ventilation died ( 1 , 3 ). A recent meta-analysis, however, found that the mortality rate for ICU patients has fallen to approximately 40% as the pandemic has progressed, suggesting improvements in treatments and system resources ( 4 ).…”
mentioning
confidence: 99%
“…Concerning mortality, our data are slightly higher than the values reported in the literature (54.4%). In fact, in a recent metanalysis on 24 observational studies, in patients with completed ICU admissions with COVID-19 infection, combined ICU mortality (95%CI) was 41.6% (34.0-49.7%) [48]. To note, the in-ICU mortality from COVID-19 is far higher than usually seen in ICU admissions with other viral pneumonias.…”
Section: Discussionmentioning
confidence: 95%